2021
DOI: 10.3390/cancers13061439
|View full text |Cite
|
Sign up to set email alerts
|

How Does Endometriosis Lead to Ovarian Cancer? The Molecular Mechanism of Endometriosis-Associated Ovarian Cancer Development

Abstract: Numerous epidemiological and histopathological studies support the notion that clear cell and endometrioid carcinomas derive from ovarian endometriosis. Accordingly, these histologic types are referred to as “endometriosis-associated ovarian cancer” (EAOC). Although the uterine endometrium is also considered an origin of endometriosis, the molecular mechanism involved in transformation of the uterine endometrium to EAOC via ovarian endometriosis has not yet been clarified. Recent studies based on high-throughp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 85 publications
0
28
0
1
Order By: Relevance
“…EMs can be anatomically divided into three sub-groups: superficial peritoneal endometriosis, deeply infiltrating endometriosis, and ovarian endometriosis (O-EMs) [ 2 ]. Notably, O-EMs is accompanied by an elevated risk of ovarian cancer [ 3 ], impaired ovarian reserve, and sterility [ 4 ], as well as the failure of in vitro fertilization [ 5 ]. EMs, as a benign disease, present similar biological characteristics with cancers like invasive and migratory properties, development of local and distant foci, and resistance to apoptosis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…EMs can be anatomically divided into three sub-groups: superficial peritoneal endometriosis, deeply infiltrating endometriosis, and ovarian endometriosis (O-EMs) [ 2 ]. Notably, O-EMs is accompanied by an elevated risk of ovarian cancer [ 3 ], impaired ovarian reserve, and sterility [ 4 ], as well as the failure of in vitro fertilization [ 5 ]. EMs, as a benign disease, present similar biological characteristics with cancers like invasive and migratory properties, development of local and distant foci, and resistance to apoptosis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between endometriosis and ovarian cancer, especially in clear cell carcinoma or endometrioid carcinoma, led to an interest in the role of somatic mutations in genes implicated in ovarian cancer [ 86 , 87 ]. With regard to cancer-associated gene mutations in endometriosis, KRAS , ARID1A , PIK3CA, and PPP2R1A are frequently noted [ 88 , 89 ].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…The impact of these mutations on the development of endometriosis is complex and highlights the need for further evaluation. Moreover, while the association between endometriosis and ovarian cancer has already been examined in numerous studies [ 88 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ], the effect of these mutations on the prevalence of PP has not been reported. Further studies are warranted to examine the effect of these mutations on the prevalence of PP.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Several studies have shown that endometriosis is one of the risk factors for ovarian cancer [ 8 ], and a proportion of ovarian cancers have been shown to originate from 0.5 to 1% of cases of ovarian endometriosis [ 9 , 10 ]. Ovarian endometriosis may present a risk for ovarian malignant lesions according to gene expression and miRNA alterations [ 11 , 12 ], and is always managed with the prevention of carcinogenesis [ 13 ]. Immunity and inflammation are thought to be strongly associated with carcinogenicity [ 14 , 15 ]; however, no studies have shown how long ovarian cancer takes to develop from ovarian endometriosis.…”
Section: Introductionmentioning
confidence: 99%